2018
DOI: 10.1080/02688697.2018.1426720
|View full text |Cite
|
Sign up to set email alerts
|

Medically induced hypertension, hypervolaemia and haemodilution for the treatment and prophylaxis of vasospasm following aneurysmal subarachnoid haemorrhage: systematic review

Abstract: There is currently insufficient evidence to determine the efficacy or non-efficacy of intravenous volume expansion, medically induced hypertension or blood transfusion for the treatment or prophylaxis of vasospasm following SAH. All of these approaches have been associated with adverse events, of unclear incidence. The current evidence base therefore cannot be used to reliably inform clinical practice. This is a priority for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…16,23 Consequently, intravenous volume expansion is widely used to treat and prevent delayed cerebral ischaemia after SAH, although efficacy has not yet been demonstrated. 24,25 Our study has the advantage of a high response rate with representation from 31 of 32 (97%) adult neurosurgical units in the UK and Ireland. We did not assess intra-unit variability, but asked units to give a consensus of their usual practice and it is possible that there is within unit as well as between unit variability in investigation and management.…”
Section: Discussionmentioning
confidence: 99%
“…16,23 Consequently, intravenous volume expansion is widely used to treat and prevent delayed cerebral ischaemia after SAH, although efficacy has not yet been demonstrated. 24,25 Our study has the advantage of a high response rate with representation from 31 of 32 (97%) adult neurosurgical units in the UK and Ireland. We did not assess intra-unit variability, but asked units to give a consensus of their usual practice and it is possible that there is within unit as well as between unit variability in investigation and management.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews and metaanalyses are also available. [26][27][28][29] Interventions include both systemic 27 and local 2628,29 endovascular treatments aiming at improving cerebral perfusion and oxygen delivery. Our algorithm is detailed in Figures 1 and 2.…”
Section: Diagnosis and Management Of DCImentioning
confidence: 99%
“…However, it is associated with significant complications and the current literature does not support its use. 29,46,47 Of the components, hypertensive therapy has the most supporting evidence. 27,39,48,49 A recent retrospective observational study of 300 patients with DCI found that hypertensive therapy was associated with a reduction in both cerebral infarcts and poor clinical outcomes.…”
Section: Management Of Vasospasm and Delayed Cerebral Ischemiamentioning
confidence: 99%